Grain Size Analysis on Pure and Zn-doped Ilmenite Magnesium Titanane Powders - Ermawati, Frida U.; Suasmoro, S.; Pratapa, Suminar (Omega: Jurnal Fisika dan Pendidikan Fisika, 2017)
Ilmenite structured of magnesium titanate (MgTiO3)-based ceramic has been the favorite candidate for microwave frequency applications, such as in mobile and satellite communication systems, dielectric resonantor, antenna, radar and global positioning system (GPS) due to the excellent dielectric performance, i.e. a moderate permittivity (εr ∼ 17.6) together with a high quality factor (Q × f) of ∼ 33,768 GHz at 10 GHz and a near zero temperature coefficient of the resonance frequency (τf ∼ -48 ppm/oC) (Wang, et al. 2012). Many efforts have been made to fabricate MgTiO3-based ceramics with improved performance, including preparation of nanostructured MgTiO3 powder as the ceramic precursor. Having powder with nanoscale grain size is very advantageous in the ceramic fabrication because the total surface area of contact between nanoscale grains are much larger than the similar total surface area of contact between microscale grains, and the presence of the larger surface energy in the nanopowder turns out to be a driving force of sintering; in this case, to reduce the free energy of the system during the sintering process. Sintering process is a process of firing of compact powder to produce ceramic with controlled microstructure, reduced porosity and enhanced properties. This paper reported the work to analyze the grain sizes in a series of Mg1-xZnxTiO3 for x = 0 - 0.5 (MZT0 - MZT0.5) powders prepared from Mg, Zn and Ti metals powders and hydrochloric acid (Merck©) using a facile wet mixing method. The Zn-doped samples were calcined at 550 oC, while that of the zinc free sample was at 700 oC. Bright field-transmission electron microscope (BF-TEM), MAUD-based x-ray diffraction (XRD) and particle size analyzer (PSA) analysis methods were occupied to measure the average grain sizes of the calcined powders, as well as the particle size distribution, and the results were compared. Discussion on the phase formation and thermal events during thermal treatment of the system was also provided.